Edukasi Pengelolaan Sampah Tingkat Rumah Tangga sebagai Bentuk Pencegahan Stunting di Kalurahan Caturharjo Bantul - Nur Syarianingsih Syam (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
Current human activities are the cause of the accumulation of waste. Waste generated from community activities can come from households, agriculture, offices, industry, and so on. Based on previous research, waste that is not properly handled will cause environmental damage, produce odors, and risk the spread of diseases that are agents or sources of infection that cause stunting in children. The purpose of this community service is to provide education on waste management to prevent cases of stunting in children. The methods used in the educational activities are lectures and question and answer sessions. Composting training is conducted using a practical method. Educational media used leaflets and composting practice materials using household waste leftovers from the community service targets. The target community service was 20 housewives in the Caturharjo area. The results obtained are that the education and practice were implemented well and smoothly. The community provided a positive response to the material provided in the form of questions and answers after the educational material. There was a change in composting skills among the community members. The conclusion of this community service activity was an increase in knowledge and skills in processing household waste into composter.